Growth and body weight of free-range reindeer in western Alaska - Finstad, Greg L.; Prichard, Alexander K. (Rangifer, 2000)
Total body weight of 9749 reindeer calves and 4798 adult reindeer were measured from 1984 to 1999 on the Seward Peninsula, western Alaska, USA. Growth rates of male and female calves, and annual growth patterns of adults were determined. Male calves grew faster than female calves. Reproductive females were lighter than non-reproductive females during summer but there was no effect of reproduction on average body weights the following winter. Adult males age 3-5 were heavier during summer than winter. Castrated males weighed the same as uncastrated males in summer, but were significantly heavier in winter, and did not display the large annual fluctuations in weight typical of reproductive males and females. Growth rates were higher and body weights greater in this herd than many other cir-cumpolar reindeer populations. We suggest these kinds of physiological indices should be used to monitor the possible effects of spatial and temporal variation in population density and to evaluate changes in herding practices.